A Comparative Analysis of the Building Stock in EU and Romania - Claudiu Romila (CES Working Papers, 2013)
Buildings occupy an important role in our modern society. However, the existing buildings have a very low thermal protection, leading to high levels of energy consumption making the buildings sector among the most significant CO2 source in Europe. Even if new buildings have high performance levels, the majority of the building stock is represented by older buildings which require renovation work. The European Union has imposed important reduction of specific energy consumption in all sectors, but energy conservation in buildings remains a key element in obtaining the sustainable development as evidence of human solidarity beyond the limits of space and time. In this paper the importance of the energy reductions in the building sector is outlined and both the energy policy and building stock statistics in EU and Romania are presented. Moreover, some measures and initiatives at European level are discussed, focusing on some important themes: demography, housing stock age and energy requirements.
Keywords: A12; F64; L74; 330; construction; building sector; energy consumption; building stock Romania